Identifikasi Plankton di Sungai Pepe Bengawan Solo Jawa Tengah Yang Terkena Dampak Limbah Domestik - Dwi Safitri, Yulia, Efri Roziaty, S.Si. M.Si (2016)
This research was conducted to identify kind of plankton at Pepe river Bengawan Solo Central Java that was effected by domestic waste. This research used purpose sampling method with 2 stations there are inlet and outlet, at each station there are 3 sub station. Sampling was done 3 times with interval 1 week. The physic-chemical factors were measured included water and air temperature, pH, and humidity. The data analysis ware used included abundance index (N), diversity index (H'), evenness index (e) and dominance index (C). abundance index of plankton in inlet (1825 ind/l), outlet (2575 ind/l). Diversity index of plankton in inlet (2.2), outlet (1.4), it was mean there was low level waste at Pepe river. Evenness index of plankton inlet (1), outlet (0.7), and dominance index of plankton in inlet (0.3), outlet (0.7), it was mean there was genus of plankton that was dominant in the river because of the waste. The plankton that was found at inlet were 14 kind of plankton, 3 from Zooplankton included Euglena, Cyclops (Egg), Vorticella and 11 Phytoplankton included Epigloeosphaera, Noctiluca, Oscilatoria, Epigloeosphaera, Chlorella, Bacillaria, Lyngbia, Meridion, Nitzschia, Synura and Mycrocytis. At outlet was found 17 kind of plankton 3 from Zooplankton included Euglena, Paramaecium, Amoeba and 14 from phytoplankton included Oscilatoria, Chlorella, Bacullaria, Lyngbia, Nitzschia, Skeletonema, Volvox, Anabaena, Rhyzosolenia, Gonatozygon, Spirogyra, Meridion, Planktoniella and Merismopedia. Chlorella was genus of plankton who most were found.